1987
DOI: 10.1099/00221287-133-3-629
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterization of an Adhesin from Candida albicans

Abstract: Candida albicans produces extracellular polymeric material (EP) which contains a mannoprotein adhesin. EP isolated from culture supernatants of C. albicans GDH 2346 consisted of a mixture of glycoprotein components and inhibited yeast adhesion to buccal epithelial cells by up to 60%. Partial purification of the adhesin was achieved by a two-step procedure involving chromatography of EP on concanavalin A-Sepharose and DEAE-cellulose. The purified adhesin inhibited adhesion to buccal cells 30 times more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 23 publications
4
89
0
1
Order By: Relevance
“…Also, the ultrastructural findings about the adhesion of Candida albicans were noticed by Howlett & Squier and Tokunaga et al (1986) mentioning the mechanisms of interaction between Candida albicans and the epithelium cell surface. However, evidences suggested that the cell wall protein is the most important molecule for the Candida adhesion (Critchley & Douglas, 1987;. Our data confirmed that between bacteria surface and the epitelial cell membrane there are a complex network of filamentous materials clearly noted by transmission electron microscopy and in three-dimensional HRSEM images.…”
Section: Resultssupporting
confidence: 75%
“…Also, the ultrastructural findings about the adhesion of Candida albicans were noticed by Howlett & Squier and Tokunaga et al (1986) mentioning the mechanisms of interaction between Candida albicans and the epithelium cell surface. However, evidences suggested that the cell wall protein is the most important molecule for the Candida adhesion (Critchley & Douglas, 1987;. Our data confirmed that between bacteria surface and the epitelial cell membrane there are a complex network of filamentous materials clearly noted by transmission electron microscopy and in three-dimensional HRSEM images.…”
Section: Resultssupporting
confidence: 75%
“…The A-strain cells cultivated in YNB-Gal for 5 d at 27 and 37°C grew in the budding yeast phase. [1][2][3] We already reported that the A-strain cells decreased the growth rate by both the changes in pH, pH 5.6 to 2.0, 11) and temperatures, 27°C to 37 and 40°C, 14) in YSLM. Based on the present results, we can state that the cell growth of the A-strain in the YNB-Gal was influenced by the severe conditions such as the low nutrition, the acidic pH, and the high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In 1981, Douglas et al reported that yeast nitrogen base medium (Difco) containing 500 mM galactose (YNB-Gal) is useful for the studies of the adhesion to acrylic surfaces 1) and buccal epithelial cells 2,3) of C. albicans, and recently, of the biofilm formations. 4) They and others 5) mentioned that the protein portrion of the mannoprotein adhesin of the yeast is more important than the carbohydrate moiety.…”
mentioning
confidence: 99%
“…2) Douglas et al 3,9,22) also reported that during the course of the adhesion studies of C. albicans cells to epithelial cells, the yeast cells cultured with the YNB-Gal produces an extracellular polymeric material which contains a mannoprotein adhesin. They suggested that the protein portion of the mannoprotein adhesin is more important than the carbohydrate moiety in mediating yeast attachment to the buccal epithelial cells.…”
Section: Adherence To Hela Cells Of A-strain Cells Cultured With Two mentioning
confidence: 99%